Classical BSE in Great Britain: Review of its epidemic, risk factors, policy and impact. (April 2023) - Alarcon, P.; Wall, B.; Barnes, K.; Arnold, M.; Rajanayagam, B.; Guitian, J.
Abstract: The emergence and epidemic of classical Bovine Spongiform Encephalopathy (cBSE) represents one of the most important and unique episodes in disease control of a zoonotic disease due to its novelty and its impact. Since its detection in 1986 in the United Kingdom, it has also been detected in 25 countries. The novel nature of its infectious agent and the discovery of its zoonotic potential (causing the new variant of Creutzfeldt-Jakob disease in humans) caught the food industry, policy makers, scientific community and consumers off guard, with concerns over massive human exposure and health impact. Thirty-five years later, and following the feed bans of mammalian protein to livestock in 1996, the epidemic is now in its final stages, with expectations of occasional cases emerging until the year 2026. In the last six years, two cBSE cases from animals Born After the Reinforced feed Ban (BARB) have been identified in Scotland and England, delaying their application for BSE Negligible status. This paper provides a current and historical analysis of the cBSE epidemic situation in Great Britain and review the policies implemented, its impact and the possible factors explaining the occurrence of new cases. The analysis and review reinforce the hypothesis that cBSE BARB cases occurrence may not be spontaneous, yet there remains much uncertainty of their aetiology. To date, 181, 122 cBSE cases have been detected in Great Britain, of which 178 are BARB cases; and 178 human cases of the new variant of Creutzfeldt-Jakob have been diagnosed. The disease triggered major policy responses in the country, and worldwide, that have transformed the industry and our approach to animal health. Almost all its impact originated from societal reactions to the disease, from disposal of animals and products, to reduction of the national herd and its production efficiency, losses through trade restrictions and reduction in market prices and consumers' confidence, hardening of cleaning and control procedures in farms and hospitals, generation of heavy government investment plans through numerous support, surveillance and research schemes, and political and societal changes. BSE is an example of major system shock to a food industry, but which experience has resulted in better traceability systems of animals, increased capacity to develop robust diagnostic methods, numerous lessons learnt on policy coordination, implementation and communication, increased society awareness on food systems and overall improved the country's preparedness to future epidemics.